Professional Code of Ethics for Managing Interreligious Cohesion in the Digital Era - Agus, Guruh David (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2025)
A professional code of ethics is a written guideline that affirms values, norms, and professional conduct. It clarifies professional ethics, prevents bias, safeguards integrity, and builds public trust. Binding in nature, any violation is subject to sanctions and must be upheld by all members of the profession. Individuals in any vocational field, especially those engaged with religious affairs, are equally obliged to honor their professional code of ethics. On World Human Rights Day 2024, Imparsial observed that religious actors in Indonesia failed to strengthen social cohesion, while state apparatuses were permissive toward groups undermining religious freedom. This research aims to answer: What if the professional code of ethics were employed as a framework of managing interreligious social cohesion in Indonesia’s digital era? This qualitative and explanatory study positions TAP MPR No. 6/2001 on the Ethics of Living as a Nation as its material object, and Jimly Asshiddiqie’s concept of the National Ethics Court (MEN) as its formal object. In Indonesia’s digital era information unavoidably finds pathways into the public sphere regardless of boundaries or constraints. As corporeal and digital actions increasingly converge the digital realm paradoxically demands corporeal solutions, particularly in contexts where ethical integrity is essential. TAP MPR No. 6/2001 encompasses socio-cultural ethics, political governance ethics, and fair legal enforcement ethics as a constitutional foundation for interreligious cohesion. Asshiddiqie envisions MEN as the culmination of Indonesia’s ethical judicial process, integrating institutional ethical systems. Guided by MEN’s framework, national ethics can reinforce the role of professional codes, offering more relevant and effective sanctions to guide religious-sector actors in upholding their ethical obligations and preserving interreligious social cohesion.